Autoinducer-2 plays a crucial role in gut colonization and probiotic functionality of Bifidobacterium breve UCC2003. - Steven E A Christiaen (Public Library of Science (PLoS), 2014)
In the present study we show that luxS of Bifidobacterium breve UCC2003 is involved in the production of the interspecies signaling molecule autoinducer-2 (AI-2), and that this gene is essential for gastrointestinal colonization of a murine host, while it is also involved in providing protection against Salmonella infection in Caenorhabditis elegans. We demonstrate that a B. breve luxS-insertion mutant is significantly more susceptible to iron chelators than the WT strain and that this sensitivity can be partially reverted in the presence of the AI-2 precursor DPD. Furthermore, we show that several genes of an iron starvation-induced gene cluster, which are downregulated in the luxS-insertion mutant and which encodes a presumed iron-uptake system, are transcriptionally upregulated under in vivo conditions. Mutation of two genes of this cluster in B. breve UCC2003 renders the derived mutant strains sensitive to iron chelators while deficient in their ability to confer gut pathogen protection to Salmonella-infected nematodes. Since a functional luxS gene is present in all tested members of the genus Bifidobacterium, we conclude that bifidobacteria operate a LuxS-mediated system for gut colonization and pathogen protection that is correlated with iron acquisition.